IMPLEMENTING MORAL EDUCATION THROUGH AL-GHAZALI'S PERSPECTIVE IN ISLAMIC STUDIES: A CASE STUDY AT ELEMENTARY SCHOOL IN YOGYAKARTA - Aulia, Ridha; Prastowo, Andi; Fathunnajih, Fathunnajih; Ayu Saputri, Diah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
The moral crisis is happening to students in Indonesia. This is evidenced by several criminal cases involving children and adolescents of school age. The purpose of this research is to find out how moral education is implemented in Islamic education learning in grade VI at SDN Sleman, Yogyakarta, based on al-Ghazali's perspective. This research was a case study. The data collection methods used in this research were observation, interview, documentation, and literature study. The research subjects were an Islamic education teacher and students of SDN Sleman Yogyakarta. The results showed that the Islamic education teacher at SDN Sleman Yogyakarta had implemented moral values in Islamic education learning. However, the surrounding environment is the biggest obstacle in instilling moral values in students. Abstrak: Krisis moral sedang terjadi pada pelajar di Indonesia, hal ini dibuktikan dengan beberapa kasus kriminalitas yang melibatkan anak-anak dan remaja usia sekolah. Tujuan penelitian ini adalah untuk mengetahui bagaimana implementasi pendidikan Akhlak dalam pembelajaran Pendidikan Agama Islam (PAI) di Kelas VI SDN Sleman Yogyakarta dengan perspektif al-Ghazali. Jenis penelitian ini adalah studi kasus. Metode pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara, dokumentasi, dan studi pustaka. Subjek penelitian terdiri dari seorang guru dan siswa PAI SDN Sleman Yogyakarta. Hasil penelitian menunjukkan bahwa guru PAI SDN Sleman Yogyakarta sudah menerapkan nilai-nilai moral dalam pembelajaran PAI namun lingkungan sekitar menjadi kendala terbesar dalam menanamkan nilai-nilai moral pada siswa.